Kurikulum Merdeka dan Relevansinya dalam Pembelajaran Bahasa Arab di Era Modern - Annas, Azwar; Baihaqi J, Ahmad Soffa; Salsabila, Sabrina Ayu; Febriyanto, Muhammad (MAN Insan Cendekia Siak, 2025)
This article aims to discuss the development function of the Merdeka Curriculum in Arabic language learning and its comparison with the 2013 Curriculum. This research uses a qualitative approach with a library research method, which analyzes various relevant literature sources regarding the implementation and development of the Merdeka Curriculum in the context of Arabic language learning. The results show that the implementation of the Merdeka Curriculum provides freedom for students to develop their potential through a more flexible approach and is based on interests and talents. The Merdeka Curriculum also allows students to improve their Arabic language skills in the context of religion, science, and culture. Compared to the 2013 Curriculum, the Merdeka Curriculum provides more space for students to be creative and develop 21st century competencies such as collaboration, communication, critical thinking, and creativity. This study concludes that the development and implementation of the Merdeka Curriculum in Arabic language learning can improve the quality of education and produce students who are more competent and ready to face the challenges of the times.